Beta-amyloid influences the content and trafficking of beta-amyloid precursor protein via Na,K-ATPase-Src kinase positive feedback loop - Petrushanko, Irina Y.; Lisitskii, Denis R.; Filonov, Filipp A.; Leonova, Olga G.; Mitkevich, Vladimir A.; Strelkova, Maria A.; Makarov, Alexander A. (Frontiers in Pharmacology, 2025)
Beta-amyloid (Aβ) is an important factor in the development of pathology in Alzheimer’s disease. Level of beta-amyloid precursor protein (APP) is increased in neurites with age and in Alzheimer’s disease model mice. However, it is unclear whether Aβ can affect APP levels in cells. The aim of this study was to evaluate the effect of Aβ on the level and trafficking of APP in human neuroblastoma cells and to identify the role of cardiotonic steroid (CTS) ouabain in this process. Western blot analysis revealed that 30-min incubation of the cells with 100 nM Aβ increased APP levels by 75%. Confocal microscopy showed that Aβ alters APP trafficking, promoting its movement into neurites. This effect establishes a positive feedback loop that accelerates Aβ formation in neurites. The rise in APP was associated with Src kinase activation triggered by Aβ binding to Na,K-ATPase. Notably, Src kinase inhibition completely blocked the Aβ-induced increase in APP, indicating that beta-amyloid effect on APP is mediated by Src kinase activation. Furthermore, 100 nM CTS ouabain, a specific Na,K-ATPase ligand, significantly decreased Aβ′s impact on APP and Src kinase activation. Given that CTS are naturally present in the human body, these findings are important for developing therapeutic strategies to counteract Aβ-driven APP accumulation and for understanding the role of endogenous CTS in regulating Aβ formation.